Dolphin adventure : a true story - Grover, Wayne; Fowler, Jim (New York : Greenwillow Books, 1990)
A diver describes how he encounters and gains the trust of a family of dolphins and saves the life of their baby.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
5.4
5.4
3-6.
Keywords: Dolphins -- Juvenile literature; Wildlife rescue -- Juvenile literature; Dolphins; Wildlife rescue; Dolphins; Wildlife rescue